Relationships Between University Students' Gender and Physical Activity (PA) and Their Exercise Self-Schemas, Processing of PA-Related Information, and PA Decision-Making. Issue 1 (February 2022) - Park, In Kyoung; Kim, Youngho
In the current study, we investigated the effects of gender and regular physical activity (PA) on PA decision-making and speed of information processing. We enrolled 110 university students ( M age = 20.91, SD =2.28 years) in an experiment involving two tasks and a questionnaire. One of the two tasks assessed how much participants agreed with presented PA words and phrases and the other task predicted behavior and responses to future situations. We collected and measured the participants' choices and the time they took to make them. The questionnaire, the International Physical Activity Questionnaire (IPAQ), consisted of exercise self-schema and PA questions. We conducted a 2 (gender: male or female) ×2 (regular PA or not) multivariate analysis of variance (MANOVA) and found statistically significant differences between variables as a function of participants' gender (λ = .66, p < .001) and regular PA engagement (λ = .51, p < .001). In a regression analysis, we also found gender differences [males showed relationships between agreement with PA information and information processing speed for decisions on future behavior ( R 2 = .31, F = 12.50); females showed relationships between their exercise self-schema ( R 2 = .26, F = 18.18) and regular PA such that, in the non-regular PA group, exercise self-schema was related to reaction time in making decisions on future behavior ( R 2 = .29, F = 11.23), and in the regular PA group, agreement with PA information was related to reaction time for PA-related words, and agreement with non-PA information ( R 2 = .29, F = 8.91)]. These results highlight the need to consider participant characteristics when designing exercise interventions, and we present supplementary data regarding exercise self-schemas, decision-making, and the speed of processing PA information.